Legal Reasons Underlying Demonopolization by State-Owned Enterprises in Indonesia - Putu Samawati Saleh (Faculty of Law, Sriwijaya University, Indonesia, 2019)
Demonopolization policy towards PT. PLN (Persero) and PT. Pelindo (Persero) conducted by the Indonesian government is aimed at enhancing efficiency, the effectiveness of state-owned enterprises (SOEs), as well as global competitiveness. The rationale in determining the demonopolization policy towards the two SOEs is based on the concept of neo-liberalism market economy, which promotes efficiency and effectiveness on free market competition. The concept of neo-liberal economics is contrary to the concept of democratic economics. The concept of democratic economics based on the 1945 Constitution of the Republic of Indonesia prioritizes fair efficiency. It is the reason for the Constitutional Court to return monopoly rights to PT. PLN (Persero) as an electricity provider in Indonesia. The argue of monopoly policy or demonopolization policy of SOEs is the main problem that will be elaborated through normative research methods (documentary research) by using secondary data as the main data. Problem analysis was done by qualitative juridical through of statute approach, philosophy approach, and history of law approach. This paper provides the reason of the policy of monopoly exemption on SOEs business activities, as well as the foundation of SOEs demonopolization policy taking into consideration the constitutional basis of Article 33 of the 1945 Constitution. The concept of demonopolization of SOEs is a new one that has never been described in the Indonesian literature. As a result, the demonopolization of SOEs does not divert SOEs into private companies but rather attempts to present competitors to SOEs to be able to compete in fair competition. In another side monopoly of SOEs can be implemented towards managing important production branches that control the livelihoods of many people. It is evidence of the state’s role in ensuring the welfare of its people.